Literature Review: Metode Komputasi Numerik untuk Analisis Gelombang Elektromagnetik - Nabila Husna Shabrina (Ultima Computing : Jurnal Sistem Komputer, 2017)
This paper reviews the conceptual background and some application of numerical computational method for electromagnetic waves. In this literature review, our discussion is limited to Finite Element Method (FEM), Finite Difference Time Domain (FDTD) Method, and Method of Moment (MoM). Definition and characteristic of each method is explained, including the theoretical principles along with strength and weakness for every method. The method for solving electromagnetic problems can be selected based on the object’s shape, researcher’s domain concerned, and Maxwell equation associated with the problem. By reading this paper, readers will not only grasp the theoretical explanation but also gain the big picture of each numerical computational method. Indeks Terms— FEM, FDTD, MoM, Numerical Computational Method